ANALISIS PERAN IRONI DAN KELAKAR DALAM MENYAMPAIKAN KRITIK SOSIAL PADA PROGRAM MEET NITE LIVE METRO TV: KAJIAN PRAGMATIK - Vivi Alfiani; Israwati Amir; Nanik Handayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of irony and humor and to analyze their pragmatic functions as strategies for conveying social criticism in METRO TV’s Meet Nite Live program. The study was motivated by the widespread use of humor, satire, and irony in digital media as a means of conveying criticism of various social phenomena. This study employs a qualitative approach using content analysis. The research data consists of utterances containing irony and humor in 30 episodes of Meet Nite Live obtained from METRO TV’s official YouTube channel. Data collection was conducted through observation, transcription, note-taking, and data classification, while data analysis was based on Grice’s (1975) theory of conversational implicatures and Leech’s (1983) principles of politeness. The results show that 1,087 utterances were identified, consisting of 473 instances of irony and 614 instances of humor. The forms of irony identified included verbal irony (152 instances) and situational irony (321 instances), while the forms of humor included puns (51 instances), analogies (82 instances), hyperbole (94 instances), parody (29 instances), absurdity (39 instances), and association (319 instances). Research findings indicate that irony and humor serve as pragmatic strategies for indirectly criticizing public policy, the behavior of officials, bureaucracy, and various forms of social inequality. Furthermore, these two forms of discourse function as means of social control, vehicles for public reflection, and educational tools packaged through humor, thereby enabling critical messages to be received more effectively by the